Unlocking the zinc isotope systematics of iron meteorites - Bridgestock, L.; Williams, H.; Rehkämper, M.; Larner, F.; Giscard, M.; Hammond, S.; Coles, B.; Andreasen, R.; Wood, B.; Theis, K.; Smith, C.; Benedix, Gretchen; et al. (Elsevier Science BV, 2014)
Zinc isotope compositions (δ66Zn) and concentrations were determined for metal samples of 15 iron meteorites across groups IAB, IIAB, and IIIAB. Also analyzed were troilite and other inclusions from the IAB iron Toluca. Furthermore, the first Zn isotope data are presented for metal–silicate partitioning experiments that were conducted at 1.5 GPa and 1650 K. Three partitioning experiments with run durations of between 10 and 60 min provide consistent Zn metal–silicate partition coefficients of ∼0.7 and indicate that Zn isotope fractionation between molten metal and silicate is either small (at less than about ±0.2‰±0.2‰) or absent. Metals from the different iron meteorite groups display distinct ranges in Zn contents, with concentrations of 0.08–0.24 μg/g for IIABs, 0.8–2.5 μg/g for IIIABs, and 12–40 μg/g for IABs. In contrast, all three groups show a similar range of δ66Zn values (reported relative to ‘JMC Lyon Zn’) from +0.5‰+0.5‰ to +3.0‰+3.0‰, with no clear systematic differences between groups. However, distinct linear trends are defined by samples from each group in plots of δ66Zn vs. 1/Zn, and these correlations are supported by literature data. Based on the high Zn concentration and δ66Zn ≈ 0 determined for a chromite-rich inclusion of Toluca, modeling is employed to demonstrate that the Zn trends are best explained by segregation of chromite from the metal phase. This process can account for the observed Zn–δ 66Zn–Cr systematics of iron meteorite metals, if Zn is highly compatible in chromite and Zn partitioning is accompanied by isotope fractionation with Δ66Znchr-met≈−1.5‰≈−1.5‰. Based on these findings, it is likely that the parent bodies of the IAB complex, IIAB and IIIAB iron meteorites featured δ 66Zn values of about −1.0 to +0.5‰+0.5‰, similar to the Zn isotope composition inferred for the bulk silicate Earth and results obtained for chondritic meteorites. Together, this implies that most solar system bodies formed with similar bulk Zn isotope compositions despite large differences in Zn contents.